2012
DOI: 10.1007/s12155-011-9174-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Yield and Nutrient Responses of Switchgrass to Phosphorus Application

Abstract: Increasing desire for renewable energy sources has increased research on biomass energy crops in marginal areas with low potential for food and fiber crop production. In this study, experiments were established on low phosphorus (P) soils in southern Oklahoma, USA to determine switchgrass biomass yield, nutrient concentrations, and nutrient removal responses to P and nitrogen (N) fertilizer application. Four P rates (0, 15, 30, and 45 kg Pha −1 ) and two N fertilizer rates (0 and 135 kg Nha −1 ) were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 27 publications
(34 reference statements)
5
45
2
1
Order By: Relevance
“…Schmer et al [17] measured annual average biomass yields of 5.2 to 11.1 Mg ha −1 of switchgrass when managed as a biomass energy crop on marginal cropland in the northern Great Plains, USA. Even greater yields on marginal lands in Oklahoma were shown by Kering et al [8], with switchgrass producing 16.0 Mg ha −1 during the fifth year of production. Along newly constructed highways in West Virginia with rocky soils, switchgrass achieved good cover and soil stabilization after 2 years, although yields were not measured [21].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Schmer et al [17] measured annual average biomass yields of 5.2 to 11.1 Mg ha −1 of switchgrass when managed as a biomass energy crop on marginal cropland in the northern Great Plains, USA. Even greater yields on marginal lands in Oklahoma were shown by Kering et al [8], with switchgrass producing 16.0 Mg ha −1 during the fifth year of production. Along newly constructed highways in West Virginia with rocky soils, switchgrass achieved good cover and soil stabilization after 2 years, although yields were not measured [21].…”
Section: Introductionmentioning
confidence: 84%
“…Determining economically optimum N application rates will help switchgrass producers maximize profits with high yields while reducing fertilizer and environmental costs. Unfortunately, there is no consensus on the amount of nutrients, particularly N, to apply to a field for switchgrass growth [8,16] because the amount varies with soil type and location [7]. The amount of N required by switchgrass is a function of the desired yield, N concentration of the biomass, potential productivity of the site, soil nutrient supply, and management practices [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that systems with N applications did not realize statistically greater yields .0001 † The letters represent harvest system, the first number is kg of N ha −1 and second number is kg of K 2 O ha −1 ‡ P values are based on Fisher's protected F tests § Means reported for yield, total cost, gross revenue, and net return for the feedstock production systems within a row marked with the same letter are not significantly different based on an LSD test (P <0.05) ¶ Costs of fertilizer was estimated assuming a base-case N price of $1.43 kg −1 and a K 2 O price of $1.17 kg −1 # Revenue was calculated using a base-case feedstock price of $83 Mg −1 than systems without N applications, which is in contrast to what was found by previous studies [7,14]. However, we point out that these studies were not conducted in K-deficient soils.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive soil testing has revealed that a substantial percentage of acres in the southern Great Plains are deficient in potassium (K), primarily those in the eastern areas that are comprised of sandy soils and receive greater than 889 mm of rainfall each year [2]. At present, most switchgrass fertilizer management studies have mainly focused on the benefits and costs associated with nitrogen (N) fertilizer as the primary limiting nutrient [3][4][5] and a few studies have focused on phosphorus (P) fertilizer [1,6,7]. However, little information is available regarding the costs and benefits associated with N and K fertilization on switchgrass produced in K-deficient soils.…”
Section: Introductionmentioning
confidence: 99%